Voting in Hiring Committees: Which "Almost" Rule Is Optimal? - Eyal Baharad; Leif Danziger (Global Labor Organization (GLO), 2018)
We determine the scoring rule that is most likely to select a high-ability candidate. A major result is that neither the widely used plurality rule nor the inverse-plurality rule are ever optimal, and that the Borda rule is hardly ever optimal. Furthermore, we show that only the almost-plurality, the almost-inverse-plurality, and the almost-Borda rule can be optimal. Which of the "almost" rules is optimal depends on the likelihood that a candidate has high ability and how likely committee members are to correctly identify the abilities of the different candidates.
Keywords: D71; 330; Committee decisions; Scoring rules; "Almost" voting rules